Emulsions stabilized by nanofibers from bacterial cellulose: New potential food-grade Pickering emulsions. (January 2018) - Zhai, Xichuan; Lin, Dehui; Liu, Dongjie; Yang, Xingbin
Abstract: In the present work, we investigated the formation and stability of Pickering emulsions stabilized by nanoparticles generated from bacterial cellulose (BC) by hydrochloric acid hydrolysis. The resulting particles, called nanofibers, presented a ribbonlike shape with diameters of 30–80 nm and range in length from 100 nm to several micrometers. The obtained nanofibers showed good hydrophilic and lipophilic properties and had significant ability to reduce the surface tension of oil/water droplets from 48.55 ± 0.03 to 34.52 ± 0.05 mN/m. The oil-in-water Pickering emulsions with a peanut oil concentration of 15% (v/v) were stabilized by only 0.05% (w/v) nanofibers and displayed a narrow droplet size distribution and high intensity with an average droplet size of 15.00 ± 0.82 nm. The morphological studies confirmed the nano-scaled droplets of emulsions. The effects of pH values and temperatures on the creaming ability and physical stability were also evaluated by zeta-potential and droplet sizes. Results showed that emulsions displayed relatively lower creaming ability at pH < 7, while displayed optimal physical stability and dispersibility at pH ≥ 7. The temperature (20–100 °C) and time-dependent test (0–4 weeks) indicated that the Pickering emulsions stabilized by only 0.05% (w/v) nanofibers displayed excellent stability. Due to the sustainability and good bio-compatibility of nanofibers from BC, the developed emulsions stabilized by low concentration of nanofibers can be used as new food-grade Pickering emulsions and have great potential to deliver lipophilic bioactive substances in food industry. Graphical abstract: Highlights: Nanofibers have significant ability to decrease the surface tension of oil/water droplets. Only 0.05% nanofibers are able to stabilize oil/water system. Nanofibers stabilized Pickering emulsions display excellent dispersed properties for 4 weeks. Nanofibers stabilized emulsions can be used as new potential food-grade Pickering emulsions.